Arabic Language Teaching Strategies to Strengthen Islamic Literacy in Islamic Boarding Schools - Abidah, Zakiyatul; Rohman, M. Fathor (Research and Community Service Institute (LP2M) of Institute Pesantren Sunan Drajat, 2025)
This study aims to analyze Arabic teaching strategies in strengthening Islamic literacy at Sunan Drajat Lamongan Islamic Boarding School. As the main language in Islamic sources such as the Qur'an, Hadith, and classical books, mastery of Arabic is the key for students to understand Islamic teachings in depth. Therefore, effective teaching methods are needed so that Islamic literacy can develop optimally. This study uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study show that the Arabic teaching strategy at the Sunan Drajat Islamic Boarding School includes the qawā'id wa tarjamah (rule-based translation) method, muhādatsah (active conversation), tahfiz mufradat (vocabulary strengthening), and dirāsah al-kutub (study of classical books). In addition, technology-based approaches are beginning to be applied through the use of digital media in learning. The results of this study show that the strategy applied is able to improve the ability of students to understand Islamic texts in Arabic. However, there are still challenges in terms of variety of methods and more optimal use of technology.